2011
DOI: 10.1007/s00404-011-2148-7
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient and outpatient loop electrosurgery excision procedure for cervical intraepithelial neoplasia: a retrospective analysis

Abstract: Purpose To determine whether the outpatient loop electrosurgical excision procedure (LEEP) conization (out-LEEP) is as effective and safe as inpatient LEEP conization (in-LEEP) with regard to the complete removal of cervical dysplasia, recurrence-free survival and post-operative morbidity. Methods 233 patients were included in this retrospective cohort study from January 2002 to December 2007. 181 had outpatient treatment and 52 inpatient treatment. We used Mann-Whitney U test, two-sided Fisher's exact test, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In fact, a non-surgical treatment alternative avoids the alteration of cervical anatomy, thereby enabling a therapeutic approach that preserves reproductive health for young women 4 and also avoids the adverse events specifically associated with surgical treatment for cervical HSIL. 4,[13][14][15][16][17]…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a non-surgical treatment alternative avoids the alteration of cervical anatomy, thereby enabling a therapeutic approach that preserves reproductive health for young women 4 and also avoids the adverse events specifically associated with surgical treatment for cervical HSIL. 4,[13][14][15][16][17]…”
Section: Discussionmentioning
confidence: 99%
“…Adequate management of cervical dysplasia is an important step in cervical cancer prevention [10]. The cure rates following LLETZ have been broadly investigated with respect to patientsʼ age, parity, size and grade of lesion, cone size and volume, as well as the use of various LLETZ technique modifications [2,4,[11][12][13]. However, data on surgeonsʼ colposcopic experience and its influence on specimen quality, the presence and diagnostic significance of the artifacts have been inadequately studied.…”
Section: Histology and Margin Status Of Specimensmentioning
confidence: 99%
“…Large loop excision of the transformation zone (LLETZ) is a commonly used technique for managing women with pathological changes on the uterine cervix, which has gained worldwide acceptance due to its numerous advantages [1][2][3][4]. Unlike ablative methods, LLETZ allows histological examination of the excised tissue [1][2][3][4]. However, LLETZ causes thermal damage of specimens [5], due to the use of electricity, which simultaneously cuts and coagulates the tissue [6].…”
mentioning
confidence: 99%
“…Moreover, the authors suggested that treatment of CIN using LEEP and CC combined could have less abnormal cervical cytologic findings in women who had incomplete excision of their initial lesion compared to LEEP alone. Meanwhile, previous studies reported positive margin rates of 16 to 46.3% after LEEP [ 7 , 11 13 ]. Although several earlier studies have reported that replicate surgical specimens of patients with involved resection margins (RMs) frequently have no residual neoplasia [ 14 17 ], the margin status of conization specimens is considered to be an important predictor of residual neoplasia [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%